Shifting metaphors in direct-to-consumer genetic testing: from genes as information to genes as big data - Paula Saukko (New Genetics and Society, 2017)
This article analyses shifts in metaphors in direct-to-consumer genetic testing, analyzing the websites and select media coverage of the nutrigenetic testing company Sciona (2000–2009) and the personal genome service 23andMe (2006–). Sciona represented genes and communication through the classical metaphor of information; genes coded for disease, and this information was transmitted from the expert company to the consumers. 23andMe represented genes and communication through a new metaphor of big data; genes were digital data or a resource that was browsed, correlated with other data, uploaded and retrieved across lay customers, websites and companies. In terms of understanding health 23andMe tests and research still cast genes as coding for disease to be mitigated by lifestyle change and targeted drugs. However, rendering genes digital data or resources changed their social and economic meaning; genes could be circulated, shared and traded, which legitimized 23andMe’s business model of consumer genetics and private biobanking.